Prediction of mass and radii of anisotropic polytropic compact objects with Buchdahl-I metric - S. A. Mardan; A. Zahra; Muhammad Bilal Riaz; Rubab Manzoor; Adnan Malik (European Physical Journal C: Particles and Fields)
Abstract In this article, we discuss several compact objects (GW 190814, PSR J0952-0607, PSR J0030+0451, PSR J0740+6620,   GW 170817,   PSR J1614-2230,   PSR J2215+5135, and 4U 1608-52) to predict their masses and radii. A generalized polytropic stellar model within the framework of general relativity is derived by employing the Buchdahl-I metric. All the physical quantities such as energy density, radial, and tangential pressure are well behaved, continuous and no singularity is observed. The obtained results are compatible with observational data for compact objects under consideration. The physical stability of this model is determined by using generalized hydrostatic equilibrium condition, energy conditions, causality conditions and Herrera’s cracking technique. We observe that our model fulfills all of the requirements for being a physically realistic model.